2003
DOI: 10.1051/rnd:2003024
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of bovine oocytes: Current status and recent developments

Abstract: -The cryopreservation of oocytes of most animal species remains a challenge due to their complex structure. Equilibrium freezing is not satisfactory because oocytes seem to be damaged by exposure for several minutes to temperatures near 0 ºC. Therefore, cryopreservation of oocytes by vitrification -especially the use of very high cooling rates of oocytes suspended in extremely small volumes of various cryoprotective additive modifications -seems the most appropriate method. oocyte / bovine / cryopreservation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 47 publications
0
31
0
3
Order By: Relevance
“…Although cryopreservation of mammalian oocytes has been successful, the effectiveness of oocyte cryopreservation in some species, including bovine, is still low because of complex structure, high chilling sensitivity and low membrane permeability (Massip, 2003;Prentice and Anzar, 2011). Recently, DNA damage in the oocyte has been found after cryopreservation and this could be one of the reasons for reduced developmental ability of cryopreserved oocytes (Stachowiak et al, 2009;Men et al, 2003a,b).…”
Section: The Effect Of Cryopreservation On Oocytesmentioning
confidence: 99%
“…Although cryopreservation of mammalian oocytes has been successful, the effectiveness of oocyte cryopreservation in some species, including bovine, is still low because of complex structure, high chilling sensitivity and low membrane permeability (Massip, 2003;Prentice and Anzar, 2011). Recently, DNA damage in the oocyte has been found after cryopreservation and this could be one of the reasons for reduced developmental ability of cryopreserved oocytes (Stachowiak et al, 2009;Men et al, 2003a,b).…”
Section: The Effect Of Cryopreservation On Oocytesmentioning
confidence: 99%
“…However, oocytes can also be cryopreserved at the metaphase II stage of maturation. During the metaphase II stage, the cumulus cells surrounding the oocyte are expanded, microfilaments of actin are involved in cell shape and movements, and microtubules form the spindle apparatus (Massip, 2003). Moreover, cryopreservation of oocytes necessitates the success of the following steps: in vitro maturation, in vitro fertilization and embryo culture.…”
Section: Cryopreservation Of Oocytesmentioning
confidence: 99%
“…Coulter [28] reported that manipulation of spermatozoa provides opportunities for the predetermination of sex of resulting offspring, the introduction of foreign DNA into oocytes and formation of transgenic individuals. The cryopreservation of oocytes of most animal species remains a challenge due to their complex structure [29]. Using these techniques and new ones, one can control the structure of a newborn herd in the future and direct it to the needs of that future time.…”
Section: Me Et Th Ho Od Ds S L Li Iv Ve E a An Ni Im Ma Al Ls Smentioning
confidence: 99%